Design of a Z-scheme g-C3N4/CQDs/CdIn2S4 composite for efficient visible-light-driven photocatalytic degradation of ibuprofen. (April 2020) - Liang, Mingxing; Zhang, Zhaosheng; Long, Run; Wang, Ying; Yu, Yajing; Pei, Yuansheng
Abstract: A novel Z-scheme photocatalyst consisting of acidified graphitic carbon nitrogen (ag-C3 N4 )/carbon quantum dots/CdIn2 S4 (CN/CQDs/CIS) was successfully synthesized via a one-step hydrothermal method. The optimized CN-2/CQDs-3/CIS exhibited significantly improved photocatalytic performance in the degradation of ibuprofen under visible-light irradiation. Based on a series of characterizations, the ag-C3 N4 and CQDs were distributed uniformly on the surface of the cubic spinel structure of CIS, with intimate contact among the materials. This intimate heterogeneous interface facilitated the migration of photogenerated carriers, further leading to enhanced photocatalytic performance. These results also indicated that the CQDs not only connect ag-C3 N4 with CIS through covalent bonds but also enhance the visible-light adsorption. According to the analysis of the UV–vis diffuse reflectance spectra (DRS) and Mott-Schottky curves, the mechanism of the Z-scheme heterojunction is proposed. The CQDs serve as electron mediators and transfer the electrons in the conduction band (CB) of ag-C3 N4 to recombine with the holes in the valence band (VB) of CIS in the Z-scheme, leading to the enhanced separation efficiency of the photogenerated electrons in the CB of ag-C3 N4 and the holes in the VB of CIS. The pollutant IBU was degraded by h +, ·O2 − and ·OH, as determined by electron paramagnetic resonance (EPR) analysis. Graphical abstract: The CQDs serve as a bridge to not only connect ag-C3 N4 with CIS through covalent bonds but also transfer the electrons in the Z-scheme heterojunction, further leading to enhanced photocatalytic performance. Image 1 Highlights: A novel CQDs-based Z-scheme photocatalyst was successfully developed. The optimized catalyst exhibited significantly enhanced photocatalytic performance. The mechanism of the Z-scheme heterojunction was proposed. CQDs served as an electronic mediator to transfer electrons in Z-scheme heterojunction. Abstract : This work further investigates the unique features of carbon quantum dots as an electron transfer mediator for fabrication of Z-scheme photocatalyst for degrading ibuprofen.